Exilio y Renovación Transferencia política del socialismo chileno en Europa Occidental, 1973-1988 - Perry Fauré, Mariana (Ariadna Ediciones, 2020)
Process of the renewal of Chilean socialism after the 1973 coup. Ideological and political transformations in view of the recovery of democracy in Chile